THE ROLE OF YELLOW STICKING TRAPS FOR ESTIMATION OF LEAF HOPPER Empoasca decedens POALI ON DIFFERENT STRAINS OF POPLAR TREES IN MOSUL - M. Mohammed; W. Alkhafa (Mesopotamia Journal of Agriculture)
The study was conducted in the plantation of poplar research station of horticulture & forestry in Rashidia – Mosul in 2002 , it was noticed that the presence of leaf hopper on poplar trees from the beginning of May up to the end of December .The results showed that the population density of the insect which attracted to yellow sticky trip reached maximum number in October on the strains under study, the strain populus deltoides 618 was more sensitive than other s P.d. 470,P.d. 479 & R-110 and its general means were 279.56, 255.02 , 205.6 & 144.28 insects respectfully . The statistical analysis showed significant differences between strains, date of sampling and monthly populations , in addition there were non significant positive correlation between insects numbers of strain with the weekly temperature (-0.06112) , and also non significant negative correlation with the weekly relative humidity (-0.25398) .For the monthly numbers ,the correlation was negative and non significant with temperature (-0.08191) ,but it was positive and significant with the relative humidity(0.57001)